Continuity Analysis of Passenger-Centric Metrics and ‎Economic Outcomes in TNSTC (Town Bus) Services - Babima , M; Kunal, Kishore; Anand, S. T.; Madeshwaren, Vairavel (International Journal of Accounting and Economics Studies, 2025)
Passenger road transport continues to be a critical enabler of economic participation and regional mobility across India. This study extends ‎prior research on public transport satisfaction by evaluating the economic and service delivery performance of Tamil Nadu State Transport ‎Corporation (TNSTC–Town Bus) operations in the city of Madurai, a prominent urban hub in South Tamil Nadu. The research adopts a ‎structured questionnaire-based survey involving 200 respondents across diverse socioeconomic segments. It investigates six key service ‎quality dimensions: punctuality, fare fairness, staff behavior, vehicle condition, route convenience, and crowd management. The ‎hypotheses tested include the impact of each factor on overall passenger satisfaction, analyzed using ANOVA, Chi-square tests, ‎correlation matrix, multiple linear regression, and factor analysis. The findings reveal that punctuality, route convenience, and fare fairness ‎significantly influence commuter satisfaction, while crowd density and vehicle conditions show moderate effects. Staff behavior was ‎observed to be a differentiating factor between daily and occasional users. Age, income, and purpose of travel moderately interact with ‎satisfaction, but do not act as primary drivers. The paper proposes a responsive service enhancement model combining economic ‎feasibility with real-time route optimization and passenger feedback analytics. This continuity study contributes to the broader discourse ‎on regional public transport efficiency and economic service planning, especially within the framework of sustainable urban mobility‎.
Keywords: Public Transport; Service Quality; Passenger Satisfaction; TNSTC; Urban Mobility; Transport Economics; Madurai